Petalidium mannheimerae (Acanthaceae), a new species from Namibia and South Africa, with notes on the taxonomic identity of P. parvifolium - Swanepoel, Wessel; Nanyeni, Leevi; van Wyk, Abraham E. (Phytotaxa, 2022)
Petalidium mannheimerae, here described as a new species, is only known from the Gariep Centre of Plant Endemism in southern Namibia and northwestern South Africa. Apparently first collected in 1961, it grows on arid hillsides and in drainage lines. Diagnostic morphological characters for P. mannheimerae include the rigid, cylindrical distal stems, grey-brown or yellow-brown bark, puberulent vegetative parts with sparsely scattered but robust glandular and eglandular trichomes, and the solitary white flowers with the unexpanded part of the corolla tube shorter than the expanded part. A comparison of some of the more prominent features to differentiate Petalidium mannheimerae from its morphologically most similar relatives is provided. Based on IUCN Red List categories and criteria, a conservation assessment of Vulnerable VU D1 is recommended for the new species. Herbarium specimens of P. mannheimerae have long been misidentified as P. parvifolium, a rarely collected species from east-central Namibia and west-central Botswana. Lectotypes are designated for three taxa, namely P. parvifolium, P. parvifolium var. angustifolium (a synonym of P. linifolium), and P. wilmaniae (a synonym of P. parvifolium).